Intravenous Infusion of Human Adipose Mesenchymal Stem Cells Modifies the Host Response to Lipopolysaccharide in Humans: A Randomized, Single-Blind, Parallel Group, Placebo Controlled Trial. (20th August 2018) - Perlee, Desiree; van Vught, Lonneke A.; Scicluna, Brendon P.; Maag, Anja; Lutter, René; Kemper, Elles M.; van 't Veer, Cornelis; Punchard, Marie A.; González, Jesús; Richard, Marie Paule; Dalemans, Wilfried; Lombardo, Eleuterio; et al.
Abstract : In experimental models, mesenchymal stem cells (MSCs) can modulate various immune responses implicated in the pathogenesis of sepsis. Intravenous injection of lipopolysaccharide (LPS) into healthy subjects represents a model with relevance for the host response to sepsis. To explore the use of MSCs in sepsis, we determined their effect on the response to intravenous LPS in a randomized study in 32 healthy subjects with four treatment arms: placebo or allogeneic adipose MSCs (ASCs) intravenously at either 0.25 × 10 6, 1 × 10 6, or 4 × 10 6 cells/kg; all subjects received LPS intravenously (2 ng/kg) one hour after the end of ASC infusion (Trial Register number 2014-002537-63, clinicaltrials.gov identifier NCT02328612). Infusion of ASCs was well tolerated. The high ASC dose increased the febrile response, exerted mixed pro-inflammatory (enhanced interleukin-8 and nucleosome release) and anti-inflammatory effects (increased interleukin-10 and transforming growth factor-β release), and enhanced coagulation activation and reduced the fibrinolytic response. Blood leukocyte transcriptome analyses showed a biphasic effect of ASCs on the LPS response: at 2 hours post LPS, ASC-infused subjects displayed higher expression of genes involved in innate immune pathways, whereas at 4 hours post LPS these subjects had lower expression of innate immune pathway genes. Infusion of ASCs did not modify the "ex vivo" responsiveness of whole blood to various bacterial agonists. These results indicate that intravenous infusion of allogeneic ASCs (4 × 10 6 cells/kg) has a variety of proinflammatory, anti-inflammatory, and procoagulant effects during human endotoxemia. Further studies are needed to assess the safety and efficacy of ASCs in sepsis patients. Abstract : To explore the use of MSCs in sepsis, we determined their effect on the response to intravenous LPS in a randomized study in 32 healthy subjects with four treatment arms: placebo or allogeneic adipose MSCs (ASCs) intravenously at either 0.25 × 10 6, 1 × 10 6, or 4 × 10 6 cells/kg; all subjects received LPS intravenously (2 ng/kg) one hour after the end of ASC infusion. Primary endpoints included clinical signs and symptoms, leukocyte activation, cytokine release, activation of coagulation and vascular endothelium, genome-wide mRNA expression profiles, and ex vivo responsiveness of blood leukocytes.